Are Highly Intelligent People More Likely to Tolerate Risk in China? Evidence from China Family Panel Studies - Jing Zhang; Haijian Liu; Jiaming Xu (Discrete Dynamics in Nature and Society)
Understanding the correlation between cognitive ability and risk preferences is crucial for promoting technological progress and innovation in China. This study aims to investigate this relationship using survey data from the China Family Panel Studies. The results reveal a significant positive correlation between cognitive ability and risk tolerance. These findings have important implications for understanding the relationship between cognitive ability and risk preferences, as well as for informing policy decisions in areas such as financial investments and entrepreneurship incentives.